Distribution and Interrelationship of Differentiated, Degenerated and Surviving Spikelets on Panicle Branches in Rice (Oryza sativa) (Bangladesh Rice Journal, 2014)
The present investigation evaluated distribution pattern of differentiated, degenerated and surviving spikelets and interrelationship of spikelets on the basis of their position on rachis branches in a panicle of both japonica and indica cultivars. Distribution of differentiated spikelets on primary brances (PBs) and secondary brances (SBs) followed 1:1 ratio in the japonica cultivars and 1:2 or more than 2 in the indica ones irrespective of plant types revealed the genetic factor had the more influence on the observed distribution pattern in both japonica and indica cultivars. The percentage of degenerated spikelets to the differentiated ones on PBs was slightly higher in the japonica (4.2%?8.3%) than in the indica (0.5%?6.6%) cultivars. The degenerated percentage of differentiated spikelets on SBs varied more widely in the indica (11.9%?56.2%) than in the japonica (26.1%?48.2%) cultivars, although average was almost the same (37.7% in the japonica and 38.9% in the indica cultivars). Correlation coefficients showed that the increase of differentiated spikelets on PBs strongly increase the number of surviving spikelet per panicle or on PBs per panicle in both cultivar groups. But this was not significantly increase the number of degenerated spikelets on PBs but showed possibility of increase the number of degenerated spikelets on SBs per panicle in both cultivar groups. Increased number of differentiated spikelets on SBs substantially increased the numbers of both surviving and degenerated spikelets on SBs per panicle and showed weak negative (in japonica) and positive (in indica) significant correlation with the percentage of degenerated spikelets on SBs. The number of surviving PBs was highly correlated with the surviving spikelets on PBs per panicle. Therefore, above results imply that the increase of differentiated spikelets on PBs of both cultivar groups and on SBs in the japonica group could sustain the survivility of spikelets with higher number of differentiated PBs per panicle.DOI: http://dx.doi.org/10.3329/brj.v17i1-2.20901Bangladesh Rice j. 2013, 17(1&2): 49-63